Plasma D-Dimer as a Disease Progression Marker in Operable Breast Cancer (Journal of Surgical Sciences, 2026)
Background: Identifying reliable prognostic markers is crucial for early intervention and improved survival in breast cancer. Plasma D-dimer, a fibrin degradation product, has been implicated in cancer progression and metastasis. This study was conducted to evaluate the significance of plasma Ddimer as a disease progression marker in Bangladeshi women with operable breast cancer, and its correlation with tumor size, histological grade, lymph node status, and hormone receptor profile.Methods: An observational cross-sectional study was conducted at Dhaka Medical College Hospital between July and December 2018. Fifty women aged 20–60 years with operable breast cancer were enrolled using systematic random sampling. Clinical, radiological, and histopathological evaluations were performed. Plasma D-dimer levels were measured and analyzed against clinicopathological variables using SPSS v20.Results: The mean age of patients was 46.2±14.2 years. The majority (42%) were aged 41–50 years. Left breast involvement predominated (58%), and 52% presented with diffuse whole-breast disease. Most tumors were ³T3 stage (76%). Elevated D-dimer levels correlated significantly with larger tumor size (mean 3.22 mg/ml for T4), higher histological grade (2.67 mg/ml for grade III), lymphovascular invasion (2.5 mg/ml vs. 0.5 mg/ml, p